MANAJEMEN PESERTA DIDIK BERBASIS PESANTREN DALAM PEMBENTUKAN KARAKTER DI MADRASAH ALIYAH NURULHUDA PRINGSEWU TAHUN PELAJARAN 2016/2017 - Agustrianti, Melisa; Wahyudi, Feri; Masrur, Moh. (STIT Pringsewu, 2018)
AbstractThis study aims to describe: (1) Implementation of Pesantren Based Student Management in Character Formation, (2) Success of Character Building Through Pesantren Based Student Management, And (3) Supporting Factors And Impediments of Pesantren Based Student Management in Character Building in MA Nurul Huda Pringsewu.The result of research shows that pesantren boarding school management in character formation in MA Nurul Huda Pringsewu use three strategy step, that is moral knowing, moral feeling, and moral action. And in its application using four management functions, namely; (2) Organizing: establishing an organizational structure with the Asatidz Council Pondok Pesantren Nurul Huda Pringsewu (3) Implementation: launches four programs, namely: (a) formal system, (b) non-formal system, (c) organizational system, (d) vocational system. (4) Supervision: direct supervision and through evaluation of Headmaster along with Nurse and Board of Asatidz Pondok Pesantren Nurul Huda Pringsewu.The successful management of pesantren-based learners in the formation of these characters can be seen from the achievement of existing indicators in the field, that is, there are ten values of characters that are formed: religious, honest, tolerance, discipline, self-reliant, friendly / communicative, democratic and respectful. While supporting factors and inhibiting the management of pesantren-based learner in the formation of character in MA Nurul Huda Pringsewu, supporting factors ayaitu: (a) motivation kyai, ustadz / teacher, and students who support, (b) adequate learning media, (c) climate and the tradition of pesantren that supports, (d) the figuration of kyai and ustadz / teacher as concrete examples, (e) vocational programs with adequate media, and (f) intimate communication between institutions and society. The inhibiting factors include: (a) inadequate learning media care standards, (b) pesantren traditions with simplicity, (c) lack of critical culture, (d) uneven activity effectiveness, and (e) negative external cultures.